Peran Koperasi Simpan Pinjam Pembiayaan (KSPP) Syariah Tadbiirul Ummah dalam Mengembangkan UMKM di Lingkungngan Kampus IPB Bogor - Harits Syukrillah; Ade Marfuddin; Hermawan Timbas (STES Islamic Village, 2022)
Small and Medium Enterprises (SMEs) in Indonesia are facing with a number of major challenges. The demand Crisis due to Covid-19 is still experienced by many MSME actors, especially those who sell their products to consumers who are affected by Covid-19. Therefore, MSMEs need the role of other institutions in overcoming these problems. Cooperatives are one of the organizations that are present to assist MSME players to build their businesses to be more developed. One of them is the Tadbiirul Ummah Sharia Cooperative in Bogor. This research aims to find out the role of the Cooperative in helping to increase the growth of MSME businesses around their operational offices on the Bogor IPB Campus. The method used for data analysis in this study is to use a qualitative approach using interview and observation instruments to obtain the required data. The results of this study are that the existence of cooperative and its role in an area will greatly affect the economic development of the community. This can be proven by the finding that the Tadbirul Ummah Cooperative has provided financial assistance that has an effect on the development of the business level of small and micro business actors. This cooperative provides financing that is needed by business actors so that their business can run and develop better.